WARC: The First and the Last - Cesky, T. (Radioengineering Society, 1992)
WARC-92 was the last of its kind. The "Last Big WARC". The process was very difficult and some refer to the conference as consensus by exhaustion, clearly demonstrating one of the reasons for restructuring the ITU. CEPT (Conference europeenne des Administrations des postes et des telecommunications) countries entered this Conference with their ECPs - European Common Proposals - extending thus the potential for frequency harmonization within Europe. The CEPT preparation for, and participation in, WARC-92 was the most effective yet and built on lessons learned at a number of previous WARC's. This WARC was the first Conference where CEPT was present with its new expanded membership. European countries therefore had to be constantly on the guard to avoid giving the impression that CEPT was an inflexible political block with 32 potential votes. Lastly, the Soviet Union together with its satellites was, for the first time, no longer in evidence, although the Russian Federation was generally supported by other countries from within the new Commonwealth of Independent States. The objective of this article is to point out principal WARC decisions from European point of view.